2016
DOI: 10.1159/000446288
|View full text |Cite
|
Sign up to set email alerts
|

Fissure Integrity and Volume Reduction in Emphysema: A Retrospective Study

Abstract: Background: One-way endobronchial valves (EBVs) relieve symptoms of emphysema, particularly in patients without collateral ventilation between the target and adjacent lobes. Pretreatment knowledge of fissure integrity could serve as an aid in indicating EBV interventions. Objective: This study aimed to investigate the relationship between software-measured lung fissure integrity and clinically relevant lung volume reduction (≥350 ml) in emphysema patients treated with one-way EBVs using a lobar exclusion strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…This proportionally low rate of pneumothoraces is caused by a low rate of complete fissures, leading to CV and incomplete lobar occlusion [20]. Due to an improved patient selection in consideration of catheter-based CV assessment [21,22,23,24] and CT-based analysis [24,25], the rate of pneumothoraces increases up to 25-30%, as in the current analysis.…”
Section: Discussionmentioning
confidence: 70%
“…This proportionally low rate of pneumothoraces is caused by a low rate of complete fissures, leading to CV and incomplete lobar occlusion [20]. Due to an improved patient selection in consideration of catheter-based CV assessment [21,22,23,24] and CT-based analysis [24,25], the rate of pneumothoraces increases up to 25-30%, as in the current analysis.…”
Section: Discussionmentioning
confidence: 70%
“…Applying a bimodal distribution of patients above and below a single threshold of 90% fissure completeness, the overall accuracy was 75.8%, with a sensitivity of 83.3% and a specificity of 66.7%, which was similar to the results of QCT alone in our study. The third study was performed by de Oliveira et al [16], who retrospectively analyzed 38 treated patients. They investigated the relationship between fissure completeness and clinically relevant lobar volume reduction (≥350 ml), using a QCT analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These methods are more efficient and have an improved reliability over visual methods. A recent study concluded that the optimal treatment algorithm might be a combination approach, using radiology for an anatomical classification based on fissure completeness, and a physiologic measure of airflow in patients with partially complete fissures [16]. …”
Section: Introductionmentioning
confidence: 99%
“…In a recent retrospective study (n = 38), de Oliveira et al proposed new criteria for patient selection (40). The study indicated that TLVR would not exceed 350 mL after EBV implantation in patients with an interlobular fissure that was less than 75% complete (n = 8).…”
Section: Tlvrmentioning
confidence: 99%
“…Therefore, EBV implantation in the lower lobe may have more of a benefit, but this contention needs to be verified. Several studies have indicated that EBV implantation in the left lobe was more likely to achieve a TLVR than implantation in the right lobe (40,42). This may be because the left lobe is less likely to have collateral ventilation than the right lobe (46).…”
Section: Other Predictorsmentioning
confidence: 99%